Okazjonalizmy Wasilija Szukszyna w przekładzie na język polski - Tołkaczewski, Filip (Acta Polono-Ruthenica, 2018)
The article is concerned with Shukshin’s occasionalisms and their Polish equivalents extracted from translations done by I. Bajkowska, Z. Gadzinianka, T.G. Lipszyc, E. Niepokólczycka, I. Piotrowska, B. Reszko, and A. Tyszkowska. The study material consists of 43 equivalents and is presented in three separate groups referring to structural-and-semantic, semantic as well as affixational occasionalisms. The author claims that the most common translation equivalents are either neutral or colloquial units belonging to the lowest register, for they are the most frequently used regardless of the type of occasionalisms.